Fibrinogen-like protein 1 promotes liver-resident memory T-cell exhaustion in hepatocellular carcinoma - Yang, Changjie; Qian, Qiwei; Zhao, Yudong; Huang, Bingyuan; Chen, Ruilin; Gong, Qiyu; Ji, Hao; Wang, Chenchen; Xia, Lei; You, Zhengrui; Zhang, Jianjun; Chen, Xiaosong (Frontiers in Immunology, 2023)
Abstract Background and aims: The key role of tissue-resident memory T ( TRM ) cells in the immune regulation of hepatocellular carcinoma (HCC) has been investigated and reported, but the regulatory mechanism of tumor microenvironment on TRM cells is still unclear. Lymphocyte activating gene 3 (LAG-3) is a promising next-generation immune checkpoint that is continuously expressed due to persistent antigen exposure in the tumor microenvironment. Fibrinogen-like protein 1 (FGL1) is a classical ligand of LAG-3 and can promote T cell exhaustion in tumors. Here, we excavated the effect of FGL1-LAG3 regulatory axis on TRM cells in HCC. Methods: The function and phenotype of intrahepatic CD8+ TRM cells in 35 HCC patients were analyzed using multicolor flow cytometry. Using a tissue microarray of 80 HCC patients, we performed the prognosis analysis. Moreover, we investigated the suppressive effect of FGL1 on CD8+ TRM cells both in in vitro induction model and in vivo orthotopic HCC mouse model. Results: There was an increase in LAG3 expression in CD8+ TRM cells in end-stage HCC; moreover, FGL1 levels were negatively correlated with CD103 expression and related to poor outcomes in HCC. Patients with high CD8+ TRM cell proportions have better outcomes, and FGL1-LAG3 binding could lead to the exhaustion of CD8+ TRM cells in tumors, indicating its potential as a target for immune checkpoint therapy of HCC. Increased FGL1 expression in HCC may result in CD8+ TRM cell exhaustion, causing tumor immune escape. Conclusions: We identified CD8+TRM cells as a potential immunotherapeutic target and reported the effect of FGL1-LAG3 binding on CD8+ TRM cell function in HCC.